Prevention within a pastoral strategy : assessing the ABC-model with reference to the HIV/AIDS pandemic in Swaziland - Mamba, Constance N. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2012.